Langerhans Cell Histiocytosis Presenting as a Lesser Trochanter Fracture in an Adolescent: A Case Report. Issue 1 (6th January 2023) - McCambridge, Teri Metcalf; Papakyrikos, Cole; Levin, Adam
Abstract : Case: We present the case of an 18-year-old man with right hip pain who was found to have a lytic lesion of the lesser trochanter of the right femur with cortical destruction and a lytic lesion of the left inferior pubic ramus. Additional imaging and pathology testing confirmed a diagnosis of multifocal, single-system Langerhans cell histiocytosis (LCH) of the bone. Conclusion: LCH is a rare pediatric disease most commonly diagnosed in toddlers and young school-age children. Its epidemiologic characteristics are poorly described for young adults and older adolescents, in whom clinical suspicion should be maintained when evaluating multifocal osseous lesions.